2015
DOI: 10.1051/0004-6361/201424579
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic fields at the surface of active single G-K giants

Abstract: Aims. We investigate the magnetic field at the surface of 48 red giants selected as promising for detection of Stokes V Zeeman signatures in their spectral lines. In our sample, 24 stars are identified from the literature as presenting moderate to strong signs of magnetic activity. An additional 7 stars are identified as those in which thermohaline mixing appears not to have occured, which could be due to hosting a strong magnetic field. Finally, we observed 17 additional very bright stars which enable a sensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
159
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(190 citation statements)
references
References 116 publications
15
159
0
7
Order By: Relevance
“…For example, polar cap-like starspots appear to have lifetimes of over a decade in RS CVn binaries as well as in young MS stars (Strassmeier 2009). Nevertheless, a handful of giant stars with slow rotation have been studied in the last decade with the Zeeman Doppler imaging, which allows to obtain the strength and geometry of the surface magnetic field by using new high resolution spectropolarimeters such as Narval, ESPaDOnS or HARPSpol (Aurière et al 2015). These authors found that most of the giant stars with detected magnetic fields (the longitudinal component) are undergoing the first dredge-up (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For example, polar cap-like starspots appear to have lifetimes of over a decade in RS CVn binaries as well as in young MS stars (Strassmeier 2009). Nevertheless, a handful of giant stars with slow rotation have been studied in the last decade with the Zeeman Doppler imaging, which allows to obtain the strength and geometry of the surface magnetic field by using new high resolution spectropolarimeters such as Narval, ESPaDOnS or HARPSpol (Aurière et al 2015). These authors found that most of the giant stars with detected magnetic fields (the longitudinal component) are undergoing the first dredge-up (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…According to the theoretical estimation by Aurière et al (2015) the maximum convective turnover time of KU Peg should be around τ ≈ 100 d. This would yield a moderate Rossby number of Ro ≈ 0.24, indicating that the star operates an αΩ type dynamo. However, from the time evolution of the spotted surface, especially considering the polar spots between 2006-2011, we were only able to estimate a rough cycle length of a few years.…”
Section: Summary and Discussionmentioning
confidence: 88%
“…Lèbre et al 2009;Aurière et al 2015) we carried out a comparative study by using the spectrum synthesis code SPECTRUM by R. Gray (www.appstate.edu/~grayro/spectrum/spectrum.html). We calculated synthetic spectra from our new parameters (T eff = 4440 K, log g = 2.0, v sin i = 29.4 km s −1 , [Fe/H] = −0.37, and micro-and macroturbulences of ξ mic = 1.8 km s −1 and ξ mac = 3.0 km s −1 ) and from the old parameter set taken from Lèbre et al (2009)…”
Section: Astrophysical Parameters Of Ku Pegmentioning
confidence: 99%
“…Therefore only the most massive stars are already in more advanced evolutionary stages after the main sequence. Very recently, Auriere et al (2015) reported on the detection of a magnetic field in θ 1 Tau whose unsigned longitudinal component peaked to 3 ± 0.5 G. From their measurements they find indications for a complex surface magnetic field structure.…”
Section: Characteristics Of γ Psc and θ 1 Taumentioning
confidence: 99%